When the Liver Spills Into the Chest: A Case of Thoracic Empyema Secondary to Ruptured Liver Abscess - Ume Rooman (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: A liver abscess is an accumulation of pus in the liver and is usually amoebic or pyogenic in origin. It can be life-threatening and has a mortality rate of up to 30%. If the abscess ruptures and spreads into the thoracic cavity, it can lead to pleural empyema, which can be fatal if left untreated. Case Presentation: We report on the case of an eight-year-old boy who presented with a one-month history of fever, abdominal pain, and vomiting, along with progressive respiratory distress for the past seven days. Despite receiving oral antibiotics before presentation, there was no clinical improvement. Initial imaging, including abdominal ultrasound and CXR, revealed a 10×10 cm cavity in the right hepatic lobe communicating with the pleural cavity, accompanied by complete homogeneous opacity of the right hemithorax. A subsequent chest CT scan confirmed a large hepatic abscess containing approximately 800-1000 ml of pus. The patient was admitted to the intensive care unit, started on intravenous antibiotics, and placed on mechanical ventilation for respiratory support. He underwent Video-Assisted Thoracoscopic Surgery (VATS) for surgical drainage and debridement of the empyema. Intraoperatively, a collapsed right lung and a diaphragmatic defect were identified. Postoperatively, the patient showed marked clinical improvement and was discharged on the third day after surgery. Informed consent was obtained from the patient’s guardian for reporting this case. Conclusion: This case highlights lung empyema as a rare but serious complication of a liver abscess, resulting from transdiaphragmatic extension. Prompt recognition, appropriate imaging, and timely surgical intervention, i.e., VATS, were critical in achieving a favorable outcome. Early diagnosis and management not only resolved the infection but also prevented potentially life-threatening complications. MeSH Keywords: Pleural empyema, Liver Abscess, Video Assisted Thoracic Surgery (VATS), Pyogenic Liver Abscess, Amebic Liver Abscess